Developing Employee Integrity through Organizational Culture: A Conceptual Review in the Context of Bribery Prevention - Triyani, Triyani; Narimawati, Umi; Sindrawati, Sindrawati; Winanti, Marliana B. (PINISI Discretion Review, 2025)
Employee integrity serves as the fundamental pillar for creating an ethical work environment free from bribery practices. Within organizational settings, integrity does not rely solely on formal regulations and control mechanisms; rather, it is profoundly shaped by the strength of organizational culture, which influences employees’ values, norms, and daily behaviors. Organizational culture functions as a key determinant in fostering both individual and collective ethics through a continuous process of value internalization. This article aims to develop a conceptual framework that explains how organizational culture shapes employee integrity as a preventive and sustainable mechanism for bribery prevention. Adopting a qualitative approach through a systematic and thematic literature review of academic sources and policy reports, this study identifies the dimensions of organizational culture that influence the development of integrity. The findings reveal a limited number of studies that explicitly integrate organizational culture, integrity, and bribery prevention within a single analytical framework. Therefore, this article provides a theoretical contribution by highlighting a conceptual gap that has received little attention, as well as a practical contribution for human resource management functions and compliance units in formulating sustainable, value-based anti-bribery cultural strategies.